Turner syndrome masquerading as normal early puberty - Yong Hee Hong; Young Lim Shin (Korean Society of Pediatric Endocrinology, 2014)
Approximately 50% of patients with Turner syndrome (TS) have complete loss of one X chromosome, whereas the rest of the patients with TS display mosaicism or structural abnormalities of the X chromosome. Most well-known common features are short stature and gonadal failure. Approximately one third of girls with TS may enter spontaneous puberty, but only half those completed with menarche. However, some atypical features of TS have been described. Many studies have been conducted to verify and delineate proposed loci for genes pertaining to the TS phenotype, and correlations between karyotype and phenotype. A few rare cases of precocious puberty with TS have been described. Here we describe a case of TS with the Xp22.1 deletion presenting with short final stature, early normal onset of spontaneous puberty, and Graves' disease, without short stature during puberty.